Perbandingan Model Guided Discovery Learning Dengan Kooperatif Jigsaw Dipadu Eksperimen Terhadap Keterampilan Proses Sains Siswa - As Syaffa Al Liina; Maridi Maridi; Harlita Harlita (Universitas Sebelas Maret, 2019)
This research is quasi experimental research. The research design used posttest only group design. General population is all science students of class X SMA. The research sample are the students of X-MIPA SMA as the first experiment group (the applied of Guided Discovery Learning model) that contains 30 students and X MIPA 2 as the second experiment group (The applied of Jigsaw Cooperative fused by experiment) that contains 30 students. The sampling method that used was the cluster sampling. The collecting data method used essay test for measuring student’s science process skill, observation list for evaluate syntax model activity, and school documents. Validity test that used was coefficient formula Product moment by Karl Pearson and reliability test that used was Alfa Cronbach formula. Prerequisite test analysis consisted of normality test and homogeneity test. Normality was analyzed by Kolmogorov-Smirnov test and homogeneity was analyzed by Levene’e test. The result was showed that all groups were in normal distribution and homogeneous data. The analysis data used t test with significance level 0,05. Hypothesis test by using t test showed that signification value was 0,000 < 0,05 so H0 is rejected, it means that there is a significant difference of Science Process Skills ability between the first experiment class and the second experiment class. The post test average score of the first experiment is 57,17 and the second experiment is 68,8. Based on that result, it is concluded that Jigsaw Cooperative Model fused by experiment give more significant influence toward student’s science process skill compared to Guide Discovery Learning Model.